Bandgap fibre-based curvature and temperature sensors - Seow, Ying Ming (2016)
Multi-parameter sensor has been a relatively hot topic nowadays in fibre technology. Additionally, All-Solid Photonic Bandgap Fibres (ASPBGFs) has been view as a suitable material for employing dual-parameter sensing application. This is due to its unique features such as low non-linearity and low-loss transmission spectra and etc., light is confined to the core by a photonic bandgap of the cladding. Hence, with using bandgap fibre as the basis, this project experiment ways of using processing techniques such as Fibre Bragg Grating (FBG) and Mach-Zehnder Interference (MZI), to develop a multi-parameter sensor. In particular, with the integration of FBG and MZI fabricated on the centre of the fibre sample, the sensitivity of the fibre sample to both bending test and temperature test will be investigated.